Network performance optimisation using odd and even dual interleaving routing algorithm for oil and gas pipeline networke - Subramaniam, Siva Kumar; Ikhwan Lee, Mohamad Yusry Lee; Azman, Amierul Syazrul Azril; Feroz, Farah Shahnaz; Rajkumar, Sujatha (Little Lion Scientific Islamabad Pakistan, 2022)
Wireless Sensor Network (WSN) provide promising and resilient solutions in a broad range of industrial applications, especially in the pipeline of oil and gas midstream pipeline. Such application requires a wide communication coverage area because the pipelines are usually stretched over a long distance. To fit the requirement, the sensor nodes have to be arranged in a linear formation. Performance evaluation has been carried out using reactive (AODV) and proactive (DSDV) routing protocols during the initial phases of the research. The factors causing the overall network performance to degrade as the network density increases are identified. It is mainly due to the load's increment, which will inhabit the packet queue and clog the network. These will result in packet loss, throughput unfairness, higher power consumption, and passive nodes in the network. The AODVEO reactive routing protocol is proposed to reduce the routing instabilities by splitting the traffic into (1) even-path and (2) odd with the consideration of the x-axis. The proposed routing algorithm was then compared to AODV and DSDV routing algorithms in terms of network performance with node deployment of 20,40,60,80,100,120,140,160,180 and 200. The proposed routing algorithm has shown substantial improvements in the delivery ratio (19.07% more), throughput (9 kbps more), fairness index (0.06 more), passive node's presence (30% less), and energy consumption (0.038J less) when compared to AODV on 200 nodes deployment